2012
DOI: 10.1111/j.1365-2222.2012.04014.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a CXCR2 antagonist in patients with severe asthma and sputum neutrophils: a randomized, placebo‐controlled clinical trial

Abstract: This new treatment provides an opportunity to investigate the role of neutrophils in severe asthma with potential clinical benefits. Larger studies of longer duration are needed to evaluate the impact on other outcomes of asthma including exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
196
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(200 citation statements)
references
References 27 publications
(30 reference statements)
4
196
0
Order By: Relevance
“…Daclizumab, a humanised IgG1 monoclonal antibody against the IL-2 receptor-a chain of activated lymphocytes improved FEV1 and asthma control in moderate-to-severe asthmatic adults inadequately controlled on ICS [162]. A CXCR2 antagonist, SCH527123, reduced sputum neutrophilia in severe adult asthma, and was associated with a modest reduction in mild exacerbations, but without an improvement in asthma control [163]. It is unclear whether better efficacy would have been seen with additional phenotyping as the definition of sputum neutrophilia remains unsatisfactory.…”
Section: Remarksmentioning
confidence: 99%
“…Daclizumab, a humanised IgG1 monoclonal antibody against the IL-2 receptor-a chain of activated lymphocytes improved FEV1 and asthma control in moderate-to-severe asthmatic adults inadequately controlled on ICS [162]. A CXCR2 antagonist, SCH527123, reduced sputum neutrophilia in severe adult asthma, and was associated with a modest reduction in mild exacerbations, but without an improvement in asthma control [163]. It is unclear whether better efficacy would have been seen with additional phenotyping as the definition of sputum neutrophilia remains unsatisfactory.…”
Section: Remarksmentioning
confidence: 99%
“…However, if we select the patients with neutrophil-dominant asthma, these antagonists may have effects in a similar way to anti-IL-5 Ab in eosinophil-dominant asthma. Recent studies suggested that some drugs, including macrolide antibiotics and CXCR2 Ab, are expected to have effects [48][49][50][51]. The effect of these drugs on eosinophil TBM induced by neutrophils should be examined in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This agent showed improvement in asthma scores and pulmonary function [92]. Furthermore, a CXCR2 antagonist showed modest improvement in exacerbation rate without improvement in asthma control in a subgroup of asthma patients with increased sputum neutrophils [93]. Antibodies against IL-13, lebrikizumab, showed improved pulmonary function testing but no effect on exacerbation rate or symptoms [94].…”
Section: Other Targeted Treatmentsmentioning
confidence: 99%